Higher protein intake may benefit in patients with prolonged mechanical ventilation - Chang, Chiung-Hsin; Lin, Chun-Yu; Lo, Yu-Lun; Lin, Ting-Yu; Hung, Chen-Yiu; Hsieh, Meng-Heng; Fang, Yueh-Fu; Huang, Hung-Yu; Lin, Shu-Min; Lin, Horng-Chyuan (Frontiers in Nutrition, 2024)
Patients with prolonged mechanical ventilation (PMV) is usually associated with muscle wasting and diaphragm weakness, resulting in high medical costs and mortality. Adequate energy and protein intake were beneficial in sarcopenia patients. We aimed to investigate the impact of protein intake in weaning parameters in patients with PMV.We enrolled patients with PMV (mechanical ventilation ≥6 h/day for ≥21 days) from a respiratory care center (RCC) of a tertiary medical center from December 2020 to October 2022, and classified them into weaning success and weaning failure groups. The patients' characteristics, nutrition records, weaning parameters and outcomes were analyzed.A total of 289 patients were included (mean age 73.5 years). Of the 289 patients, 149 were weaned successfully and 140 were not. The average protein intake was higher in the weaning success group than in the weaning failure group (1.22±0.320 versus 0.99±0.332 g/kg/day, p<0.001). No significant differences were noted in the average calorie intake and whey protein intake between the two groups. RSBI < 90 breaths/min/L (OR=2.38, p=0.045), serum albumin at 4 th week ³ 3 g/dL (OR=2.89, p=0.027), daily protein intake ≥1.01 g/kg/day (OR=8.10, p<0.001), PaO2/FiO2 (PF) ratio ³ 300 (OR=2.56, p=0.027) were independent predictors for weaning from ventilator. Weak positive correlations were found between average protein intake with PF ratio (r=0.1576, p=0.0227) and PaO2 (r=0.13359, p=0.0497).Daily protein intake had positively correlated with PF ratio and had independently benefit for weaning in patients with PMV.